2018
DOI: 10.1155/2018/2926167
|View full text |Cite|
|
Sign up to set email alerts
|

Spectroscopic and Electrochemical Properties of (1-x)[PVA/PVP] : x[MgCl2

Abstract: Blend polymer electrolytes were prepared with different wt% compositions of [PVA/PVP-MgCl2·6H2O] : x% using solution cast technique. Structural, morphological, vibrational, thermal, and ionic conductivity and electrochemical properties were studied on the prepared polymer films. XRD revealed the crystalline nature of the polymer electrolyte films. The morphology and the degree of roughness of the prepared films were analyzed by SEM. FTIR and Raman studies confirmed the chemical complex nature of the ligands, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…This means the current comes solely from electrons, i.e., the entire current is from electrons with no contribution by ions. Based on the ion transfer number values of 0.88 and 0.75 of the two samples, the main contributor of the carrying charge are ions rather than electrons [67]. Therefore, from the TNM measurement it can be concluded that PVCS4 is a preferable system for electrochemical device applications, in particular if the conductivity of the system is maximized to 10 −3 -10 −4 S/cm.…”
Section: Tnm Measurementmentioning
confidence: 94%
“…This means the current comes solely from electrons, i.e., the entire current is from electrons with no contribution by ions. Based on the ion transfer number values of 0.88 and 0.75 of the two samples, the main contributor of the carrying charge are ions rather than electrons [67]. Therefore, from the TNM measurement it can be concluded that PVCS4 is a preferable system for electrochemical device applications, in particular if the conductivity of the system is maximized to 10 −3 -10 −4 S/cm.…”
Section: Tnm Measurementmentioning
confidence: 94%
“…Following a reassessment of the published figures, the following issues were identified: Figure 1 in [1] with Figure 1 from [2]. In [1], the data is described as X-ray diffraction patterns of pure PVA/PVP blend polymer and with different wt% ratios of MgCl 2 ·6H 2 O, while in [2] the data is described as the X-ray diffraction pattern of PVA/PVP:GO (ii) Figure duplication in Figure 2B in [1] with Figure 2E from [3].…”
mentioning
confidence: 99%
“…Following a reassessment of the published figures, the following issues were identified: Figure 1 in [1] with Figure 1 from [2]. In [1], the data is described as X-ray diffraction patterns of pure PVA/PVP blend polymer and with different wt% ratios of MgCl 2 ·6H 2 O, while in [2] the data is described as the X-ray diffraction pattern of PVA/PVP:GO (ii) Figure duplication in Figure 2B in [1] with Figure 2E from [3]. In [1], the data is described as the SEM images of [PVA/PVPMgCl 2 ·6H 2 O]: x% with different wt% compositions, while in [3] the data is described as SEM images of different compositions of [PVP + MgCl 2 6H 2 O]: x%.…”
mentioning
confidence: 99%
See 2 more Smart Citations